Multibeam bathymetry processed data (Atlas Hydrosweep DS 2 echo sounder entire dataset) of RV POLARSTERN during cruise ANT-XIX/4 (PS61), Scotia Sea, South Atlantic Ocean - Schenke, Hans Werner; Dreutter, Simon; Dorschel, Boris (PANGAEA, 2025)
Multibeam data were collected during RV Polarstern cruise ANT-XIX/4 (2002-02-28 to 2002-04-01). Multibeam sonar system was Atlas Hydrographic Hydrosweep DS 2 multibeam echo sounder. Data are processed with Caris HIPS, including sound velocity correction by cross fan calibration and World Ocean Atlas 18 (https://www.ncei.noaa.gov/archive/accession/NCEI-WOA18), tidal correction with TPXO9_atlas_v5 (https://www.tpxo.net/global/tpxo9-atlas), and manual cleaning. The soundings are combined in daily files, the format is XYZ ASCII (<Lon> <Lat> <Depth in meters, positive up, relative to mean sea level>). Additional grids have been computed with depth dependent cell size to visualize the data. These grids are not meant for scientific analysis or navigation, but for overview purposes only.
Keywords: Bathymetry; Hydrosweep DS2; Multibeam; Polarstern; Scotia Sea; South Atlantic Ocean